Shapeshifting in the Venus flytrap (Dionaea muscipula): Morphological and biomechanical adaptations and the potential costs of a failed hunting cycle - Durak, Grażyna M.; Speck, Thomas; Poppinga, Simon (Frontiers in Plant Science, 2022)
The evolutionary roots of carnivory in the Venus flytrap (Dionaea muscipula) stem from a defense response to plant injury caused by e.g., herbivores. D. muscipula aka. Darwin’s most wonderful plant underwent extensive modification of leaves into snap-traps specialized for prey capture. Even the tiny seedlings of the Venus flytrap already produce fully functional, millimeter-sized traps. The trap size increases as the plant matures, enabling capture of larger prey. The movement of snap- traps is very fast, (approx. 100-300 ms) and is actuated by a combination of changes in the hydrostatic pressure of the leaf tissue with the release of prestress (embedded energy), triggering a snap-through of the trap lobes. This instability phenomenon is facilitated by the double curvature of the trap lobes. In contrast, trap reopening is a slower process dependent on trap size and morphology, heavily reliant on turgor and/or cell growth. Once a prey item is caught, the trap reconfigures its shape, seals itself off and forms a digestive cavity allowing the plant to release an enzymatic cocktail to draw nutrition from its captive. Interestingly, a failed attempt to capture prey can come at a heavy cost: the trap can break during reopening, thus losing its functionality. In this mini-review, we provide a detailed account of morphological adaptations and biomechanical processes involved in the trap movement during D. muscipula hunting cycle, and discuss possible reasons for and consequences of trap breakage. We also provide a brief introduction to the biological aspects underlying plant motion and their evolutionary background.